Optimalisasi Produksi dan Pemasaran Keripik Singkong melalui Teknologi Tepat Guna di Kelompok Sahabat Tani - Damianus Manesi; Fahrizal Fahrizal; Rohi, Jullyo G.; Putra, Tri Mandala; Klau, Aleksander O.; Maia, Jenigius A. R; Nuban, Albi; Sei, Alexander Y.; Tuka, Oliver (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This community service program was implemented to enhance the production and marketing of cassava chips by the Sahabat Tani Group in Lamea Village, Wewiku District, Malaka Regency. The main challenges faced by the partners were the use of manual slicers that produced uneven thickness, low capacity, and a risk of injury, as well as simple packaging methods that were not airtight, reducing product shelf life. To address these issues, the program introduced appropriate technologies, namely a semi-mechanical slicing machine and an electric sealer, supported by training in machine operation, packaging techniques, product labeling, and business management focused on production recording and digital marketing. The implementation method included observation, interviews, solution design, structured training, field mentoring, and participatory evaluation. The results showed an increase in production capacity from an average of 3-4 kg/day to 8-10 kg/day, improved product quality with uniform slices, extended shelf life and attractiveness through labeled packaging, and the initiation of production recording and social media based marketing. Participatory evaluation revealed that the program not only improved technical aspects but also enhanced the partners’ confidence, participation, and independence in sustainably developing their business.